LMS-DRIVEN HOTS READING MODEL FOR HIGHER EDUCATION ENHANCEMENT - Darmawan, Erlan; Thamrin, Nani Ronsani; Suwarto, Gentur Priguna (English Review: Journal of English Education, 2023)
This research aims to implement the Learning Management System of the Learning Process for developing a reading instruction model based on HOTS. Conducted the research in a private university in Kuningan, West Java, Indonesia. At present, one of the private tertiary institutions in Kuningan during COVID-19 is conducting lectures in a virtual class using Moodle in the learning process with the e-class, a part of the LMS. With the implementation of a virtual class in the form of Moodle used by the students of a private university in Kuningan, it is hoped that it can improve the reading instruction model based on higher-order thinking skills. This research is a kind of research and development or Research and Development (R&D) to produce products and test the feasibility of products, where the products developed are in the form of a reading instruction model based on HOTS using the ADDIE development model (Analysis, Design, Development and Implementation, Evaluation). The results are very effective in using this model, as seen from the test results obtained by students in the class.